2020
DOI: 10.1007/s11748-020-01341-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular compression of the left bronchus in a patient with funnel chest

Abstract: We present a case of 5 year-old female with funnel chest, by which cardiovascular structures were displaced into the left chest cavity. This caused left bronchial compression by the pulmonary artery and the descending aorta, for which an external stenting was successfully performed. The patient had features suggestive of skeletal dysplasia with tracheobronchial malacia. One possible mechanism of vascular compression could be an association of fragility of the thoracic cavity and inspiratory dyspnea, causing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additionally, our patient had pectus excavatum. The association between chest deformities and bronchial stenosis is described in the literature (14)(15)(16). It has been suggested that the costosternal retraction can be the consequence of the increased intrathoracic pressure during expiration to overcome the airway obstruction due to the CBS ( 14) and usually the deeper impression corresponds to the side of the CBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our patient had pectus excavatum. The association between chest deformities and bronchial stenosis is described in the literature (14)(15)(16). It has been suggested that the costosternal retraction can be the consequence of the increased intrathoracic pressure during expiration to overcome the airway obstruction due to the CBS ( 14) and usually the deeper impression corresponds to the side of the CBS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is questionable whether pectus excavatum is solely due to CBS. CBS, in fact, can be also caused by an abnormal thoracic configuration (17) due to complex mechanisms of vascular compression (15). Based on the clinical presentation, it could be useful to perform a full genotyping as suggested by some Authors (1), along with further diagnostic work-up, especially in the presence of features suggesting skeletal dysplasia (18).…”
Section: Discussionmentioning
confidence: 99%